Pengembangan Lapisan Komposit 3YSZ - AL2O3 Pada Substrat Inconel Dengan Metode Electrophoretic Deposition - Jeremy, Jason; Basoeki, Prita Dewi; Sugiarti, Eni (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
Nickel-based alloys, known as superalloys, exhibit high resistance to oxidation and slow deformation at elevated temperatures, making them suitable for aircraft and gas turbine applications. However, corrosion remains a challenge at temperatures exceeding 800◦C. One solution is to coat the metal with heat-resistant layers such as YSZ and Al2O3 ceramics. Previous research indicates that adding Al2O3 above 30% has a negative impact. Therefore, a study was conducted to explore coatings with 10% and 20% Al2O3 compositions using electrophoretic deposition method at voltages of 20V, 40V, and 60V onan Inconel substrate. The study found that the 20% Al2O3 coating had a porosity of 26% and a maximum hardness of 105.64 HV at 20V voltage.